Organic-inorganic hybrid fiber for micro-plastic adsorption and preparation method of organic-inorganic hybrid fiber

By functionalizing waste acetate fibers and growing hydroxyapatite nanowires, organic-inorganic hybrid fibers are prepared, which solves the problems of high cost of substrates and limited adsorption capacity in the prior art, and achieves efficient adsorption and reusability of a variety of microplastics, which has economic and environmental advantages.

CN119819265AActive Publication Date: 2025-04-15JIANGNAN UNIV

Patent Information

Application Number
CN202411759542.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-15
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

In the prior art, the substrate is costly and cumbersome, especially metal-based adsorption materials; the single adsorption mechanism or physical adsorption has limitations, and the adsorption capacity becomes weaker with consumption; the adsorption effect on microplastics of different types and functional groups is limited.

Method used

By pretreating waste acetate fibers, functionalizing two-step Schiff base cross-linking, and growing hydroxyapatite nanowires in situ on the fiber surface, organic-inorganic hybrid fibers with excellent performance were prepared to achieve the synergistic effect of multiple adsorption mechanisms.

Benefits of technology

It has achieved efficient adsorption and reusability of a variety of microplastics and textile microfibers, expanded application scenarios, and the substrate is a waste material, which is low-cost and has economical and environmental advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819265A_ABST
    Figure CN119819265A_ABST
Patent Text Reader

Abstract

The invention discloses an organic-inorganic hybrid fiber for micro-plastic adsorption and a preparation method of the organic-inorganic hybrid fiber. The preparation method comprises the following steps: (1) cleaning waste cellulose acetate for later use; (2) putting into an amine compound solution, adding a glutaraldehyde solution, and reacting; (3) treating in a mixed solution of a polyphenol solution and a Tris-HCl buffer solution; and (4) treating with a mixed solution of a calcium precursor, sodium hydroxide, a phosphorus source and the like to finally obtain the organic-inorganic hybrid fiber. According to the method, the micro-plastic is adsorbed and removed by using waste to treat waste, a theoretical basis and technical support are provided for value-added conversion of bio-based waste into a high-value-added environment-friendly functional adsorption material, and a new thought is provided for development and application of the micro-plastic adsorption material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functionalized preparation of waste fibers and microplastic adsorbents, and more specifically, relates to an organic-inorganic hybrid fiber for microplastic adsorption and a preparation method thereof. Background Art

[0002] Plastics are the most widely used, durable, cheapest and most common materials, and they play a vital role in our lives. Under the multiple effects of physical, chemical and biological forces, most plastics will decompose, break and degrade in the environment, forming tiny fragments such as microplastics (diameter <5mm) and nanoplastics (diameter <1μm). These microplastic fragments are widely present in fresh water, sea water, Antarctic glaciers, sediments, biota, soil, air, drinking water and food, and can even enter the human body through ingestion and inhalation, affecting the immune system and human health. Therefore, compared with non-degradable "white pollution" plastics, microplastics are more harmful to the environment. Common types of microplastics include polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polymethyl methacrylate (PMMA), polyamide (PA), acrylonitrile butadiene styrene (ABS), polyurethane (PUR), tire wear particles (TWP), degradable plastics (PLA, PHB, PVA, etc.), textile microfibers (synthetic microfibers FMPs mainly composed of nylon and polyester), discarded cigarette butts, etc. It is worth mentioning that FMPs released during textile washing are considered to be one of the most important sources of textile microfibers in the environment, and it is very important to take effective measures and means to control and manage microplastics.

[0003] Common microplastic treatment methods include coagulation and flocculation (electroflocculation), membrane bioreactor technology, adsorption, photocatalytic degradation, etc. Coagulation and flocculation are the more commonly used methods in sewage treatment plants. The use of coagulants, such as iron sulfate or aluminum sulfate, in the treatment process will trigger the integration of suspended particles into flocs, which will then form precipitates that can be easily separated from water. However, this technology is more effective for large-sized microplastics, and is not effective for smaller microplastics and nanoplastics. Membrane bioreactor technology is also widely used in the capture and removal of microplastics, but after primary and secondary wastewater treatment, millions of MPs still remain in the sewage. Adsorption is often used to absorb heavy metals and organic pollutants in water. At the same time, adsorption can also capture microplastics in water and wastewater. On the basis of adsorption, a photocatalyst with a catalytic effect can be introduced to generate reactive oxygen species (ROSs) while initiating the degradation of MPs.

[0004] Adsorption is considered to be a cost-effective, simple, reliable and effective method for capturing microplastics. The adsorbents currently developed for repairing microplastics in wastewater and natural water are divided into four categories: sponge / aerogel, metal-based, biochar and other adsorbents. The invention patent with patent publication number CN117143389A discloses a composite aerogel of microcrystalline cellulose / chitosan from bamboo shoot shells, which presents a stable three-dimensional cross-linked network structure and can produce electrostatic adsorption and physical bonding to PS micro-nano plastics. However, aerogels have the disadvantages of poor mechanical properties and high brittleness, which directly limit their reusability and renewability. At the same time, due to the high price of raw materials, the cost is limited. The invention patent with patent publication number CN111825241A discloses a micro-nano motor material, which undergoes a catalytic reaction driven by the fuel hydrogen peroxide, continuously generates micro-nano bubbles in the water environment, drives pollutants in the water to float to the surface of the water and is enriched in the bubble foam phase for separation. The method is simple and easy to operate, but most micro-nano motors are metal catalysts, which are not easy to recover and have poor biocompatibility. The invention patent with patent publication number CN116371388B discloses a magnetic sponge carbon for efficient adsorption of microplastics, which uses glucosamine hydrochloride as a carbon source, melamine as an activator, and magnetic metals, and is obtained by high-temperature carbonization. The magnetic adsorption of PS microplastics in a small amount of water environment is excellent, but this magnetic adsorption is not suitable for the removal of multiple microplastics in a large-scale real complex environment, and the pore size of the carbon material is small during the adsorption process, and the pores will be blocked during the rapid adsorption in the early stage, and the optimal adsorption effect cannot be achieved. The invention patent with patent publication number CN118223330A discloses a composite paper-based material for filtering micro-nano plastics, which uses a vacuum filtration method to load TEMPO-oxidized nanocellulose on the surface of the filter paper, and connects the nanocellulose and the filter paper fibers through glutaraldehyde cross-linking treatment to obtain a nanocellulose / filter paper composite paper-based material, which has excellent reusability and adsorption effects, but has poor filtration efficiency and filtration flux for microplastics of smaller size.

[0005] Waste acetate fiber accounts for a large proportion of a large amount of waste textiles, and discarded cigarette filters in the form of cigarette butts are currently the main source of waste acetate fiber, solid waste and environmental pollution source. What is more serious is that the continuous fragmentation and degradation of cellulose acetate fiber, the main component of waste cigarette butts, in complex environments will produce a large amount of microplastics, and these microplastics will attach a large amount of toxic metals and polycyclic aromatic hydrocarbons (PAH) in waste cigarette butts and penetrate into the environment, causing harm to humans and wildlife. Studies have shown that waste cigarette butts can be recycled and functionalized to obtain membranes, fibers, fiber bundles, porous carbon and other adsorption and filtration materials, which can effectively treat a large amount of pollutants in wastewater. Therefore, it is a very desirable and effective means to convert waste cigarette butts into adsorption materials for the capture and removal of microplastics. Summary of the invention

[0006] [Technical issues]

[0007] Problems existing in the existing technology: (1) The cost of the substrate is relatively high and the preparation is relatively complicated, especially for metal-based adsorption materials; (2) A single adsorption mechanism or physical adsorption has limitations, and as the adsorbent is consumed, the adsorption capacity also weakens; (3) There are limitations on the adsorption of microplastics of different types and functional groups, and most materials are only able to adsorb the broadest spectrum of PS microplastics.

[0008] [Technical solution]

[0009] In view of the above problems existing in the prior art, the present invention provides an organic-inorganic hybrid fiber for microplastic adsorption and a preparation method thereof. The present invention obtains cellulose acetate fiber by pre-treating waste acetate fiber, and obtains organic-inorganic hybrid fiber with excellent performance by two-step Schiff base cross-linking functionalization and in-situ growth of hydroxyapatite nanowires, which can adsorb and remove microplastics by "treating waste with waste". It will provide a theoretical basis and technical support for the value-added conversion of bio-based waste into high-value-added environmentally friendly functional adsorption materials, and provide new ideas for the development and application of microplastic adsorption materials.

[0010] The technical solution of the present invention is as follows:

[0011] The first object of the present invention is to provide a method for preparing organic-inorganic hybrid fibers for microplastic adsorption, comprising the following steps:

[0012] (1) Soaking the waste acetate fiber in deionized water, drying it, ultrasonically washing it in ethanol, ultrasonically cleaning it with a non-polar organic solvent, and finally cleaning it with deionized water and drying it for use;

[0013] (2) placing the waste acetate fiber treated in step (1) in an amine compound solution, stirring magnetically at room temperature for 12 hours, adding glutaraldehyde solution, adjusting the pH to 8.0, and rinsing with deionized water after the reaction is completed, and drying for standby use;

[0014] (3) placing the fiber treated in step (2) in a mixed solution of a polyphenol solution and a Tris-HCl buffer solution, stirring the mixture magnetically at room temperature, rinsing the mixture with deionized water, and drying the mixture for later use;

[0015] (4) Under mechanical stirring, ethanol and oleic acid are mixed, and calcium precursor, sodium hydroxide and phosphorus source are added in order, and the mixed solution is transferred to a Teflon-lined stainless steel reactor, and the fiber treated in step (3) is added at the same time, and the mixture is sealed and kept warm in an oven for 24 hours. After completion, the mixture is magnetically stirred three times with ethanol and deionized water respectively, and the organic-inorganic hybrid fiber is obtained after drying.

[0016] In one embodiment of the present invention, in step (1), the waste acetate fiber is one or more of waste cigarette butts and waste textile fibers.

[0017] In one embodiment of the present invention, in step (1), the waste acetate fibers are one or more of waste cigarette butts from which cigarette segments and wrapping paper have been removed, waste acetate staple non-woven fabrics, and waste textile acetate filaments.

[0018] In one embodiment of the present invention, in step (1), the soaking conditions are: temperature of 40-80° C., and time of 6-12 h.

[0019] In one embodiment of the present invention, in step (1), the mass concentration of ethanol is 75%, and 50-100 mL is ultrasonicated for 1-4 hours.

[0020] In one embodiment of the present invention, in step (1), the ultrasonic washing power in ethanol is 40-100 kHz, the ultrasonic washing is performed for 1-4 hours, and fresh ethanol is replaced every 1 hour.

[0021] In one embodiment of the present invention, in step (1), the non-polar organic solvent is one or more of cyclohexane, petroleum ether, and toluene.

[0022] In one embodiment of the present invention, in step (1), the conditions for ultrasonic cleaning with a non-polar organic solvent are: 50-100 mL ultrasonic cleaning for 1-4 h.

[0023] In one embodiment of the present invention, in step (2), the amine compound is one or more of polyethyleneimine, ethylenediamine, hexamethylenediamine, dodecylamine, and octadecylamine; and the concentration of the aqueous solution of the amine compound is 0.8-2.0 g / L.

[0024] The molecular weight of polyethyleneimine is one or more of 600, 1800, 10000, and 70000.

[0025] In one embodiment of the present invention, in step (2), the concentration of the glutaraldehyde solution is 25 wt %.

[0026] In one embodiment of the present invention, in step (2), the molar ratio of glutaraldehyde to amine compound is 1:0.5-2.

[0027] In one embodiment of the present invention, in step (2), one or more of hydrochloric acid, sodium hydroxide and sodium bicarbonate are used to adjust the pH value of the reaction solution.

[0028] In one embodiment of the present invention, in step (2), the reaction temperature is 50-80° C. and the reaction time is 1-3 h.

[0029] In one embodiment of the present invention, in step (3), the polyphenol is one or more of tannic acid, gallic acid, catechol, catechol, ellagic acid, anthocyanin, catechin, and tea polyphenol; and the concentration of the polyphenol aqueous solution is 1.0-3.0 g / L.

[0030] In one embodiment of the present invention, in step (3), the Tris-HCl buffer solution is prepared by mixing 50 mL of a 0.1 mol / L trishydroxyaminomethane solution and 14.7 mL of a 0.1 mol / L hydrochloric acid solution; the pH value of the prepared Tris-HCl buffer solution is 8.5.

[0031] In one embodiment of the present invention, in step (3), the volume ratio of the polyphenol aqueous solution to the Tris-HCl buffer is 1:0.5-1; and magnetic stirring is performed at room temperature at 300-600 rpm for 6-24 hours.

[0032] In one embodiment of the present invention, in step (4), the rotation speed of the mechanical stirring is 500-700 rpm.

[0033] In one embodiment of the present invention, in step (4), the volume ratio of ethanol to oleic acid is 1:0.5-2; and the mass concentration of ethanol is 95%.

[0034] In one embodiment of the present invention, in step (4), the calcium precursor is one or more of calcium chloride, calcium nitrate, and calcium hydroxide; and the phosphorus source is one or more of phosphorus pentoxide, phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and dipotassium hydrogen phosphate.

[0035] In one embodiment of the present invention, in step (4), the calcium precursor is added dropwise to the mixed solution of ethanol and oleic acid at a rate of 1-100 mL / min; then the sodium hydroxide solution is added dropwise to the solution of the previous step at a rate of 1-100 mL / min; finally, the phosphorus source is added dropwise to the solution of the previous step at a rate of 1-50 mL / min.

[0036] In one embodiment of the present invention, in step (4), the mass concentration of the calcium precursor is 5-20 g / L; the mass concentration of the sodium hydroxide solution is 30-50 g / L; and the mass concentration of the phosphorus source solution is 20-300 g / L.

[0037] In one embodiment of the present invention, in step (4), the mass ratio of the calcium precursor to sodium hydroxide is 1-4:6-10.

[0038] In one embodiment of the present invention, in step (4), the mass volume ratio of the treated fiber to the solution prepared in step (4) is 0.5-5 g:100-1000 mL.

[0039] In one embodiment of the present invention, in step (4), the insulation temperature in the oven is 140-160°C.

[0040] In one embodiment of the present invention, in step (4), the capacity of the Teflon-lined stainless steel reactor is one of 100 mL, 200 mL, 500 mL, and 1 L.

[0041] In one embodiment of the present invention, a 100mL hydrothermal reactor is used. This hydrothermal reaction is carried out in an oven, kept warm in the oven for a certain time at a certain temperature, then taken out and waited for cooling, and then the reactor is opened and taken out. Its reaction vessel is a polytetrafluoroethylene liner. For hydrothermal reactions that do not produce a large amount of gas, the polytetrafluoroethylene liner is required to be charged with no more than 75%, and the overall sealing must be ensured when the stainless steel jacket is used for sealing. This is a stable, fully mixed, and successful hydrothermal reaction. At the same time, the successful preparation of the sample is guaranteed.

[0042] The second object of the present invention is to provide an organic-inorganic hybrid fiber prepared by the above preparation method.

[0043] The third object of the present invention is to provide an application of the above-mentioned organic-inorganic hybrid fiber for adsorbing one or more of microplastics PS, PET, PE, PVC, PMMA, PP, and textile microfibers PA, PU.

[0044] The sizes of common microplastics and textile microfibers are 1nm-100μm.

[0045] The types of microplastics are PS, PET, PU, ​​and PA. The size of microplastics is 5-20μm and the concentration of microplastics is 0.1-2mg / mL.

[0046] Microplastics come in different sizes and shapes. Generally, fibrous ones are called microfibers, and the general source of microfibers is textile washing, so textile microfibers are a type of microplastics. Common microplastics are ordinary PE, PP, PET, PS, PMMA, and textile microfibers are mainly polyurethane PU, polyamide PA and the like.

[0047] The beneficial technical effects of the present invention are:

[0048] The present invention combines functionalized waste acetate fiber with hydroxyapatite nanowires for the first time and applies them to the removal of microplastics. The waste acetate fiber undergoes a first Schiff base reaction with amine compounds under the cross-linking action of glutaraldehyde, and a large number of amino and hydroxyl functional groups are present on the fiber surface. At the same time, a polyphenol compound with abundant phenolic hydroxyl groups is introduced, and a second Schiff base reaction occurs in an alkaline Tris-HCl solution. It is worth noting that a large number of benzene rings are introduced into the fiber surface cross-linking, which provides favorable conditions for the π-π interaction with microplastics. Finally, hydroxyapatite nanowires are in situ grown on the fiber surface at a certain temperature, providing polyhydroxyl functional groups and abundant adsorption sites, and the nanowire structure on the surface provides favorable conditions for the pore filling of microplastics. The construction of this organic-inorganic hybrid fiber realizes the synergy of multiple adsorption mechanisms, and overall achieves excellent adsorption effect and reusability of common microplastics and textile microfibers.

[0049] The present invention introduces abundant amino groups, hydroxyl groups and large aromatic ring structures through glutaraldehyde solution crosslinking and polyphenol compound self-polymerization crosslinking, and simultaneously grows hydroxyapatite nanowires in situ to prepare environmentally friendly functionalized waste acetate fiber as an adsorbent for micro-nano plastics in water.

[0050] The present invention targets micro-nano plastics with different structures and specifically introduces corresponding functional groups into the surface of waste acetate fiber. Through electrostatic interaction, hydrogen bonding, π-π interaction and pore filling, the effect of efficiently capturing and removing microplastics is achieved. At the same time, it has excellent reusability, thereby achieving the purpose of expanding multiple application scenarios.

[0051] The organic-inorganic hybrid fiber of the present invention has multiple functional groups and active adsorption sites, and can effectively adsorb different types of microplastics according to different adsorption mechanisms, and has a wide range of applications. Its substrate, waste acetate fiber, is a harmful solid waste with a wide source and low cost, and has economic advantages. By functionalizing solid waste to give it high added value, the effect of "treating waste with waste" is achieved.

[0052] The organic-inorganic hybrid fiber of the present invention has an excellent reuse effect and can be recycled and reused by a simple method, which fully embodies the modern concept of green development. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 A fiber sample diagram of preparing organic-inorganic hybrid fibers from waste cigarette butt substrates in Example 1-2;

[0054] Figure 2 is the Fourier infrared spectrum of each fiber sample in Examples 1-2;

[0055] Figure 3 is the X-ray photoelectron spectrum of each fiber sample in Examples 1-2;

[0056] Figure 4 : are electron microscope images of each fiber sample in Examples 1-2;

[0057] Figure 5 is the Zeta potential of the microplastics and various fiber samples in Examples 1-2 at pH = 7.0;

[0058] Figure 6 Thermogravimetric analysis diagrams of the fiber samples in Examples 1-2. DETAILED DESCRIPTION

[0059] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0060] The test methods involved in the following embodiments are:

[0061] Fiber sample performance test method:

[0062] Functional group analysis of fiber samples was performed using an infrared spectrometer with an attenuated total reflectance accessory, scanning in the range of 500–4000 cm -1 ; X-ray photoelectron spectroscopy was used to analyze the surface element composition and valence state changes of the fiber samples; in order to observe the overall morphology and surface morphology of the fiber samples, a scanning electron microscope was used to observe the fiber samples. Before the test, the conductive adhesive was used to cut the fiber samples into 0.5×0.5m 2 The fiber samples were fixed on the surface of the electron microscope table and vacuum-sprayed with gold at an accelerating voltage of 5 kV. The fiber samples were heated and tested in a N2 atmosphere using a Zeta potential analyzer with a test range of 30-800°C, a heating rate of 10°C / min, and a N2 flow rate of 50 mL / min. The surface charge positivity and charge of the fiber samples were characterized by a Zeta potential analyzer.

[0063] Maximum adsorption capacity test method:

[0064] In order to explore the adsorption potential of fiber adsorbents for various microplastics, the microplastics were dispersed in a mixed solution of deionized water and Tween 80 (0.5wt%) with the assistance of ultrasound. The fiber adsorbent was then weighed and placed in the above microplastic solution and shaken in a water bath at room temperature to achieve adsorption saturation. The adsorption amount was determined by the following formula:

[0065]

[0066] In the formula, m0 and m e Represent the initial weight and equilibrium weight of the fiber adsorbent, respectively. m t It refers to the weight of the fiber adsorbent extracted from the solution at a given time point. It is worth noting that the above weights refer to the weights dried to constant weight at 60°C. In addition, q e(mg g -1 ) and q t (mg g -1 ) represent the adsorption capacity at the equilibrium time point and the given time point respectively. The mass of the fiber adsorbent is m (g). The above experiment was repeated three times and the results were averaged.

[0067] The raw materials used in the following examples are:

[0068] The waste acetate fiber described in the present invention is collected from designated public smoking points and billiard halls; the polyethyleneimine: purchased from Shanghai Aladeng Biochemical Technology Co., Ltd., with a molecular weight of 1800; the tris(hydroxymethyl)aminomethane (Tris), oleic acid, tea polyphenols (TP), sodium hydroxide, ethanol, sodium chloride, sodium acetate, ether, n-hexane, methanol, sulfuric acid, and hydrochloric acid are all purchased from Sinopharm Chemical Reagent Co., Ltd.; the sodium dihydrogen phosphate dihydrate and glutaraldehyde are purchased from Shanghai Titan Technology Co., Ltd.; the calcium chloride is purchased from Shanghai Api Chemical Reagent Co., Ltd.; the polystyrene (15 μm), polyethylene terephthalate (20 μm), polyamide (10 μm), polyurethane (20 μm), polyethylene (10 μm), polymethyl methacrylate (8 μm), polypropylene (6.5 μm), and polyvinyl chloride (6.5 μm) are purchased from Shanghai Runhong International Trade Co., Ltd.

[0069] Embodiment 1:

[0070] A method for preparing organic-inorganic hybrid fibers for microplastic adsorption comprises the following steps:

[0071] (1) 0.15 g of waste acetate fiber was soaked in 60°C deionized water for 12 h, dried at 60°C, placed in 100 mL of anhydrous ethanol with a mass concentration of 75%, and ultrasonically washed at a power of 100 kHz for 2 h, with fresh anhydrous ethanol replaced every 1 h; after drying at 60°C, placed in 50 mL of cyclohexane solution, ultrasonically washed at a power of 100 kHz for 2 h, and finally rinsed three times with deionized water, dried at 60°C for standby use, and recorded as CA fiber.

[0072] (2) 0.2 g of polyethyleneimine with a molecular weight of 1800 was added to 100 mL of deionized water to prepare a PEI solution with a mass concentration of 2.0 g / L. The fiber to be used in step (1) was placed in the above solution, stirred at 300 rpm at room temperature for 12 h, and the pH was adjusted to 8.0 with 0.1 mol / L sodium bicarbonate solution. Subsequently, 8.76 mL of a 50 wt% glutaraldehyde solution was added to ensure that the molar ratio of glutaraldehyde to polyethyleneimine was 2:1. The solution was stirred at 300 rpm at 60°C for 3 h. After the reaction was completed, the fiber was washed with deionized water and dried at 60°C for use. The fiber was recorded as PEI / GA-CA fiber.

[0073] (3) Add 0.15 g of tea polyphenols to 100 mL of deionized water to prepare a tea polyphenol solution with a concentration of 1.5 g / L; add 0.6057 g of tris(hydroxymethyl)aminomethane to 50 mL of deionized water to prepare a Tris solution with a concentration of 0.1 mol / L, and add 14.7 mL of a 0.1 mol / L hydrochloric acid solution to obtain a Tris-HCl buffer solution with a pH of 8.5; mix the tea polyphenol solution with the Tris-HCl buffer solution, place the fiber to be used in step (2) in the mixed solution, stir at 300 rpm for 12 h at room temperature, wash with deionized water after the reaction is completed, and dry at 60° C. for use, which is recorded as PEI / GA / TP-CA fiber.

[0074] (4) Add 0.22 g of CaCl2 to 20 mL of deionized water and stir magnetically at 300 rpm for 10 min at room temperature to prepare a CaCl2 solution with a mass concentration of 11.0 g / L for later use; add 1 g of NaOH, magnetically stir at 300rpm at room temperature for 10min to prepare a NaOH solution with a mass concentration of 50.0g / L, and set aside; add 0.28gNaH2PO4.2H2O to 10mL deionized water, and magnetically stir at 300rpm at room temperature for 10min to prepare a CaCl2 solution with a concentration of 28.0g / L, and set aside; add 12g oleic acid to 12g anhydrous ethanol with a mass fraction of 99.5%, and mechanically stir and mix at 700rpm at room temperature, then slowly add the above CaCl2 solution at a rate of 5mL / min, and after mechanical stirring for 15min, slowly add the above NaOH solution at 5mL / min, and after mechanical stirring for 15min, slowly add the above NaH2PO4.2H2O solution at 5mL / min, and after mechanical stirring for 15min, obtain a reaction precursor solution.

[0075] (5) The precursor solution of step (4) was transferred to the polytetrafluoroethylene liner of a 100 mL Teflon-lined stainless steel reactor, and 0.6 g of fiber prepared multiple times in step (3) was placed therein, and the fiber was sealed and kept in an oven at 150°C for 24 h. After completion, the fiber was washed three times with 99.5% anhydrous ethanol at room temperature under magnetic stirring at 100 rpm, and then washed three times with deionized water to obtain an organic-inorganic hybrid fiber, which was recorded as HANWs. 150 @PEI / GA / TP-CA fiber.

[0076] Embodiment 2:

[0077] A method for preparing organic-inorganic hybrid fibers for microplastic adsorption comprises the following steps:

[0078] Same as Example 1, except that the sealing temperature in step (5) of Example 1 is adjusted to 160°C in an oven at 150°C, specifically:

[0079] The precursor solution of step (4) was transferred to the polytetrafluoroethylene liner of a 100mL Teflon-lined stainless steel reactor, and 0.6g of fiber prepared multiple times in step (3) was placed therein, sealed and kept in an oven at 160°C for 24h. After completion, it was washed three times with 99.5% anhydrous ethanol at room temperature and 100rpm magnetic stirring, and then washed three times with deionized water to obtain organic-inorganic hybrid fibers, denoted as HANWs. 160 @PEI / GA / TP-CA fiber.

[0080] The other steps are carried out according to the method of Example 1 to prepare organic-inorganic hybrid fibers that can be used for microplastic adsorption.

[0081] The physical pictures of the organic-inorganic hybrid fibers and the fiber samples prepared in Example 1-2 are as follows: Figure 1 As shown, (a) is a waste cigarette butt without removing the cigarette segment and the wrapping paper; (b) is a waste acetate fiber after multiple washings with deionized water, ethanol and non-polar organic solvents; (c) is the fiber after the first functionalization; (d) is the fiber after the second functionalization; (e) is the fiber grown with hydroxyapatite nanowires at 150°C; (f) is the fiber grown with hydroxyapatite nanowires at 160°C. It can be seen that with the two crosslinkings and the growth of hydroxyapatite nanowires, the surface of the fiber adsorbent gradually becomes rough and porous, which will be conducive to the adsorption and capture of microplastics.

[0082] Figure 2 is the Fourier transform infrared spectrum of each fiber sample in Example 1-2; Figure 2 It can be clearly seen that the fiber adsorbent after two crosslinking and growth of hydroxyapatite nanowires has a wavelength of 300-3600 cm -1 There are -OH / -NH2 peaks, which are due to the PEI polyamino cross-linking of the Schiff base reaction and the rich hydroxyl functional groups of hydroxyapatite nanowires. -1 The presence of O=C=O double bonds proves the cross-linking of glutaraldehyde. -1 and 1550cm -1 The presence of C=N and NH at 550-1100 cm -1 Multiple peaks appearing in the range belong to PO4 3- , demonstrating the successful growth of hydroxyapatite nanowires. Figure 2It can also be clearly seen that the corresponding infrared peaks of the fiber adsorbents treated at 150°C growth temperature and 160°C growth temperature are sharper. This may be because the growth temperature of 160°C is close to the glass transition temperature of waste acetate fiber, which will affect the growth stability of the fiber surface.

[0083] Figure 3 is the X-ray photoelectron spectrum of each fiber sample in Example 1-2; Figure 3 Ca2 P 、P2 P The peaks can also prove this statement. The Ca2 P 、P2 P The peak is more prominent.

[0084] Figure 4 The electron microscope images of the fiber samples in Examples 1-2 are as follows; wherein, (a) is waste acetate fiber after multiple washings with deionized water, ethanol and non-polar organic solvents, scale = 100 microns; (b) is fiber after the first functionalization, scale = 100 microns; (c) is fiber after the second functionalization, scale = 50 microns; (d) is fiber grown with hydroxyapatite nanowires at 150°C, scale = 50 microns; (e) is fiber grown with hydroxyapatite nanowires at 160°C, scale = 5 microns. It can be seen that the surface of waste acetate fiber is smooth and has obvious grooves. After two steps of functionalization, the surface has obvious coating and roughness changes, which is conducive to the adsorption of microplastics and the growth of hydroxyapatite nanowires in the next step. (d) and (e) show that the nanowires grow densely and irregularly on the fiber surface. This large specific surface area characteristic is conducive to the capture and enrichment of microplastics. At the same time, Figure 6 As shown, HANWs 150 @PEI / GA / TP—CA and HANWs 160 @The residual weight of PEI / GA / TP-CA fiber at 800°C is 20%, which is higher than the 10% residual weight of waste acetate fiber, PEI / GA-CA fiber, and PEI / GA / TP-CA fiber at 800°C, proving that the growth of hydroxyapatite nanowires will also improve the thermal stability of the fiber adsorbent.

[0085] Example 3

[0086] A method for preparing organic-inorganic hybrid fibers for microplastic adsorption comprises the following steps:

[0087] Same as Example 1, except that the sealing temperature in step (5) of Example 1 is adjusted to 140°C in an oven at 150°C, specifically:

[0088] The precursor solution of step (4) was transferred to the polytetrafluoroethylene liner of a 100mL Teflon-lined stainless steel reactor, and 0.6g of fiber prepared multiple times in step (3) was placed therein, sealed and kept in an oven at 140°C for 24h. After completion, it was washed three times with 99.5% anhydrous ethanol at room temperature and 100rpm magnetic stirring, and then washed three times with deionized water to obtain organic-inorganic hybrid fibers, denoted as HANWs. 140 @PEI / GA / TP-CA fiber.

[0089] The other steps are carried out according to the method of Example 1 to prepare organic-inorganic hybrid fibers that can be used for microplastic adsorption.

[0090] By conducting a 24-hour adsorption test on 1.5 mg / mL PS-15μm at room temperature, the adsorption amount was measured to be 491.11±10.18 mg / g. The adsorption effect is good, but the adsorption amount is lower than that at 150°C. This may be because the lower temperature will affect the nucleation and crystal formation of hydroxyapatite nanowires during the growth process, thereby affecting the microplastic adsorption effect.

[0091] Example 4: Adsorption effects of different types of microplastics

[0092] Prepare 1.5 mg / mL PS-15μm, PET-20μm, PU-20μm, PA-10μm, PE-10μm, PMMA-8μm, PP-6.5μm, and PVC-6.5μm microplastic solutions, respectively. Add 10 mL of each solution into a 15 mL glass bottle. Add 15 mg of HANWs 150 @PEI / GA / TP-CA fiber adsorbent, oscillate at room temperature for 24 hours in a water bath oscillator at 300 rpm under pH=7, and determine the maximum adsorption capacity by the above maximum adsorption test method. Specific data are shown in Table 1:

[0093] Table 1 HANWs 150 @PEI / GA / TP—CA fiber maximum adsorption capacity

[0094] Microplastics Maximum adsorption capacity (mg / g) PS-15μm 722.22±40.18 PET-20μm 593.33±43.71 PU-20μm 688.89±31.50 PA-10μm 224.44±34.21 PE-10μm 237.78±16.78 PMMA-8μm 175.56±23.41 PP-6.5μm 77.78±23.41 PVC-6.5μm 171.11±21.43

[0095] It can be seen from the table that the adsorption effect on PS-15μm is the best, and the effect on PP-6.5μm is the worst. However, the adsorption capacity for each microplastic also has certain advantages compared with the adsorption capacity of most currently published microplastic adsorbents, proving that this organic-inorganic hybrid fiber has certain adsorption and removal advantages for a wide spectrum of microplastics.

[0096] Example 5: Regeneration effect of organic-inorganic hybrid fibers after adsorption of microplastics

[0097] The fiber adsorbent after adsorption in Example 3 was collected, dissolved by adding a small amount of aqueous acetone, and cast into a film by a phase transfer method to obtain a homogeneous film with a microplastic reinforcement phase. The microplastics acted as a filling material for the pores in the film, effectively improving the strength performance of the film.

[0098] Comparative Example 1: Effect of 170℃ hydrothermal growth temperature on the preparation of fiber adsorbent

[0099] The same as Example 1, except that the sealing temperature of step (5) in Example 1 is adjusted to 170°C in an oven at 150°C. The experiment was carried out according to the above description, and the sample was taken out after the hydrothermal reaction was completed and cooled. The fiber sample was directly broken into pieces and could not be formed into fibers. This is because the glass transition temperature of acetate fiber is about 185°C. When the oven temperature is set to 170°C, the instantaneous temperature may be greater than the glass transition temperature at a certain stage, and a long time at 170°C will reduce the stability of acetate fiber, which is not conducive to the subsequent adsorption experiment of the fiber adsorbent.

[0100] Comparative Example 2

[0101] A method for preparing organic-inorganic hybrid fibers for microplastic adsorption comprises the following steps:

[0102] The same as Example 1, except that the step (1) in Example 1 is removed and the mixture is placed in 50 mL of cyclohexane solution and ultrasonically washed for 2 h at a power of 100 kHz, specifically:

[0103] 0.15 g of waste acetate fiber was soaked in 60°C deionized water for 12 hours, dried at 60°C, placed in 100 mL of 75% anhydrous ethanol, and ultrasonically washed at a power of 100 kHz for 2 hours, with fresh anhydrous ethanol replaced every 1 hour; finally, rinsed three times with deionized water, dried at 60°C for standby use, and recorded as CA fiber.

[0104] The other steps are carried out according to the method of Example 1 to prepare organic-inorganic hybrid fibers that can be used for microplastic adsorption.

[0105] The microplastic adsorption experiment was conducted on the CA fibers obtained in step (1) of Example 1 and step (1) of Example 3. The adsorption concentration of 1.5 mg / mL PS-15 μm microplastics in 24 hours was 273.33 mg / g and 366.66 mg / g, respectively. After the CA fibers were washed with non-polar solvents, the nicotine and harmful components on the surface were greatly reduced. These nicotine and harmful components are conducive to the adsorption of more microplastics. The adsorption capacity test proved this conclusion.

[0106] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.

Claims

1. A method for preparing organic-inorganic hybrid fibers for microplastic adsorption, characterized in that: The preparation method comprises the following steps: (1) Soaking the waste acetate fiber in deionized water, drying it, ultrasonically washing it in ethanol, ultrasonically cleaning it with a non-polar organic solvent, and finally cleaning it with deionized water and drying it for use; (2) placing the waste acetate fiber treated in step (1) in an amine compound solution, stirring magnetically at room temperature for 12 hours, adding glutaraldehyde solution, adjusting the pH to 8.0, and rinsing with deionized water after the reaction is completed, and drying for standby use; (3) placing the fiber treated in step (2) in a mixed solution of a polyphenol solution and a Tris-HCl buffer solution, stirring the mixture magnetically at room temperature, rinsing the mixture with deionized water, and drying the mixture for later use; (4) Under mechanical stirring, ethanol and oleic acid are mixed, and a calcium precursor, sodium hydroxide and a phosphorus source are added in order. The mixed solution is transferred to a Teflon-lined stainless steel reactor, and the fiber treated in step (3) is added. The mixture is sealed and kept warm in an oven for 24 hours. After the mixture is heated, it is magnetically stirred three times with ethanol and deionized water respectively, and then dried to obtain organic-inorganic hybrid fibers.

2. The preparation method according to claim 1, characterized in that: In step (1), one or more of the following conditions are met: Waste acetate fiber is one or more of waste cigarette butts and waste textile fibers; The soaking conditions are: temperature 40-80℃, time 6-12h; The conditions for ultrasonic washing in ethanol were: 50-100 mL for 1-4 h; The non-polar organic solvent is one or more of cyclohexane, petroleum ether and toluene; The conditions for ultrasonic cleaning of non-polar organic solvents are: 50-100mL ultrasonic cleaning for 1-4h.

3. The preparation method according to claim 1, characterized in that: In step (2), one or more of the following conditions are met: The amine compound is one or more of polyethyleneimine, ethylenediamine, hexamethylenediamine, dodecylamine, and octadecylamine; The concentration of the aqueous solution of the amine compound is 0.8-2.0 g / L; The molecular weight of polyethyleneimine is one or more of 600, 1800, 10000, and 70000.

4. The preparation method according to claim 1, characterized in that: In step (2), one or more of the following conditions are met: The concentration of the glutaraldehyde solution is 25wt%; The molar ratio of glutaraldehyde to amine compound is 1:0.5-2; Using one or more of hydrochloric acid, sodium hydroxide, and sodium bicarbonate to adjust the pH value of the reaction solution; The reaction temperature is 50-80°C and the reaction time is 1-3h.

5. The preparation method according to claim 1, characterized in that: In step (3), one or more of the following conditions are met: The polyphenols are one or more of tannic acid, gallic acid, catechol, catechol, ellagic acid, anthocyanidin, catechin, and tea polyphenols; The concentration of the polyphenol aqueous solution is 1.0-3.0 g / L; Tris-HCl buffer is prepared by mixing 50 mL of 0.1 mol / L tris(hydroxyaminomethane) solution and 14.7 mL of 0.1 mol / L hydrochloric acid solution; The pH value of the prepared Tris-HCl buffer solution is 8.

5.

6. The preparation method according to claim 1, characterized in that: In step (3), one or more of the following conditions are met: The volume ratio of the polyphenol aqueous solution to the Tris-HCl buffer solution is 1:0.5-1; The magnetic stirring time is 6-24h.

7. The preparation method according to claim 1, characterized in that: In step (4), one or more of the following conditions are met: The volume ratio of ethanol to oleic acid is 1:0.5-2; The calcium precursor is one or more of calcium chloride, calcium nitrate, and calcium hydroxide; The phosphorus source is one or more of phosphorus pentoxide, phosphoric acid, ammonium dihydrogen phosphate, sodium dihydrogen phosphate, and dipotassium hydrogen phosphate; The calcium precursor is added dropwise to the mixed solution of ethanol and oleic acid at a rate of 1-100 mL / min; the sodium hydroxide solution is then added dropwise to the solution of the previous step at a rate of 1-100 mL / min; and finally the phosphorus source is added dropwise to the solution of the previous step at a rate of 1-50 mL / min.

8. The preparation method according to claim 1, characterized in that: In step (4), one or more of the following conditions are met: The mass ratio of calcium precursor to sodium hydroxide is 1-4:6-10; The mass volume ratio of the treated fiber to the solution prepared in step (4) is 0.5-5 g:100-1000 mL; The insulation temperature in the oven is 140-160°C.

9. An organic-inorganic hybrid fiber obtained by the preparation method according to any one of claims 1 to 8.

10. An application of the organic-inorganic hybrid fiber according to claim 9, characterized in that: Used to adsorb one or more of microplastics PS, PET, PE, PVC, PMMA, PP, and textile microfibers PA, PU.

Citation Information

Patent Citations

  • Pollutant treatment method and treatment device based on micro-nano motor material

    CN111825241A

  • A magnetic sponge carbon for adsorbing microplastics, its preparation method and application

    CN116371388B

  • Preparation method of Maolong bamboo shoot shell microcrystalline cellulose / chitosan composite aerogel and application of Maolong bamboo shoot shell microcrystalline cellulose / chitosan composite aerogel in micro-plastic adsorption

    CN117143389A

  • Preparation method and application of composite paper-based material for filtering micro-nano plastic

    CN118223330A

  • Preparation method of multifunctional porous cellulose film adsorbent

    CN106732440A

Cited By

  • Multilayer biomass cellulose adsorption material as well as preparation method and application thereof

    CN121988305A